2020
DOI: 10.3126/jnprossoc.v3i1.34750
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of Dental Adhesives use among Dental Practitioners of Chitwan

Abstract: Introduction: Denture adhesive (DA) is defined as a material used to adhere a denture to the oral mucosa. It plays an important role in the retention and the functional comfort among denture wearers. There are conflicting views in dentistry regarding the use of denture adhesives in clinical practice. Therefore, the main purpose of the study is to reveal the knowledge, attitude and practices regarding denture adhesives among the dental practitioners of Chitwan district, Nepal. Materials and Methods: A 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Moreover, a previous study has shown that only 20% of the participants knew the adverse effects of zinc-containing DAs [ 28 ]. Similarly, another study reported that most general practitioners and other specialists were unaware of extended use of zinc-containing DAs, resulting in neurological damage [ 11 ]. In the present study, half of the participants thought that the improper use of DAs can cause denture stomatitis, and they thought that prolonged use of denture adhesives with ill-fitting dentures can cause residual ridge resorption.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, a previous study has shown that only 20% of the participants knew the adverse effects of zinc-containing DAs [ 28 ]. Similarly, another study reported that most general practitioners and other specialists were unaware of extended use of zinc-containing DAs, resulting in neurological damage [ 11 ]. In the present study, half of the participants thought that the improper use of DAs can cause denture stomatitis, and they thought that prolonged use of denture adhesives with ill-fitting dentures can cause residual ridge resorption.…”
Section: Discussionmentioning
confidence: 99%
“…DAs are dental materials that are used to adhere CD to the oral mucosa [ 9 , 10 , 11 ]. DAs are available in the form of pastes, powder, or adhesive pads to be placed in the denture bearing area and eliminate the space between the denture and mucosa aiding in the denture peripheral seal [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations